2017
DOI: 10.1002/hbm.23919
|View full text |Cite
|
Sign up to set email alerts
|

Reduced brain glutamine in female varsity rugby athletes after concussion and in non‐concussed athletes after a season of play

Abstract: The purpose of this study was to use non-invasive proton magnetic resonance spectroscopy (MRS) and diffusion tensor imaging (DTI) to monitor changes in prefrontal white matter metabolite levels and tissue microstructure in female rugby players with and without concussion (ages 18-23, n = 64). Evaluations including clinical tests and 3 T MRI were performed at the beginning of a season (in-season) and followed up at the end of the season (off-season). Concussed athletes were additionally evaluated 24-72 hr (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 52 publications
3
37
0
Order By: Relevance
“…Changes in MR spectroscopy have previously been reported in a subset of these rugby players; glutamine concentrations were reduced after concussion and during the off-season and may relate to an evolving shift in oxidative metabolism or microglial priming. 13 All diffusion measures within the brainstem changed significantly between the in-and off-season in contact athletes only. The FA within the brainstem was significantly related to SCAT immediate memory scores, suggesting that these pair-wise changes in brain microstructural measures are related to exposure to repetitive impacts and altered immediate memory capacity.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Changes in MR spectroscopy have previously been reported in a subset of these rugby players; glutamine concentrations were reduced after concussion and during the off-season and may relate to an evolving shift in oxidative metabolism or microglial priming. 13 All diffusion measures within the brainstem changed significantly between the in-and off-season in contact athletes only. The FA within the brainstem was significantly related to SCAT immediate memory scores, suggesting that these pair-wise changes in brain microstructural measures are related to exposure to repetitive impacts and altered immediate memory capacity.…”
Section: Discussionmentioning
confidence: 92%
“…These data were compared to longitudinal data from concussed contact athletes in a previous publication in which details of their season are described. 13,14 A total of 31 noncontact age-matched (p > 0.3) athletes were assessed during the in-season and 23 during the off-season. Noncontact athletes (i.e., rowers and swimmers) began regular training and practices while in-season data were collected (September).…”
Section: Methodsmentioning
confidence: 99%
“…Relation to previous investigations. A variety of previous investigations into the effects of sports participation, repetitive head impacts and white matter tissue properties of athletes have used the diffusion tensor (DTI) model (Bahrami et al, 2016;Basser et al, 1994;Bazarian et al, 2014;Burzynska et al, 2016;Chang et al, 2015;Chun et al, 2015;Churchill et al, 2017aChurchill et al, , 2017bDavenport et al, 2016aDavenport et al, , 2016bDavenport et al, , 2014Deng et al, 2018;Duru and Balcioglu, 2018;Gajawelli et al, 2013;Hänggi et al, 2015Hänggi et al, , 2010Jäncke et al, 2009;Koerte et al, 2012;Kuzminski et al, 2018;Lao et al, 2015;Marchi et al, 2013;Mayinger et al, 2018;McAllister et al, 2014;Merchant-Borna et al, 2016;Myer et al, 2018Myer et al, , 2016aMyer et al, , 2016bPark et al, 2015;Saghafi et al, 2018;Schlaffke et al, 2014;Schranz et al, 2018;Sollmann et al, 2018;Stamm et al, 2015;Yuan et al, 2018) . The studies investigating the effects of elite sports participation commonly report lower fractional anisotropy (FA) and higher mean diffusivity (MD) between athletes and non-athletes.…”
Section: Discussionmentioning
confidence: 99%
“…The most common SVS voxel placement reflects the fact that preclinical and postmortem studies have identified white matter diffuse axonal injury as the hallmark site of TBI injury (Su & Bell, 2015). Most often, the targeted regions have been frontal/prefrontal white matter (Maugans et al, 2012;Schranz et al, 2018;Sivák et al, 2014;Vagnozzi et al, 2010Vagnozzi et al, , 2008Walz et al, 2008); Dhandapani et al, 2014), splenium (Cecil et al, 1998;Gasparovic et al, 2009; and genu of the corpus callosum. SVS voxel placement in gray matter is also common, with most studies focusing on the cingulate gyrus (Koerte et al, 2015;Lin et al, 2012;Louis et al, 2017), dorsolateral prefrontal cortex (Dean et al, 2015;Henry et al, 2010;Poole et al, 2014;Bari et al, 2019) and primary motor cortex (Tremblay et al, 2014).…”
Section: Considerations For Study Design Multisite Studies and Recomentioning
confidence: 99%